Assessment of NEXRAD P3 data on streamflow simulation using SWAT for North Fork Ninnescah watershed, Kansas - Gali, Rohith Kumar (Kansas State University, 2010)
Radar-derived P3 data from Next Generation Radar (NEXRAD) of the National Weather Service (NWS) offer higher spatial resolution than precipitation gauge data, which might improve the accuracy of streamflow simulations using watershed models. The objective of this study was to evaluate the performance of spatially-averaged subwatershed-specific NEXRAD P3 data on streamflow simulations using Soil and Water Assessment Tool (SWAT) model. The SWAT hydrologic model was chosen for this study to simulate the hydrologic processes in North Fork Ninnescah Watershed located in south-central Kansas. A precipitation gauge station for each subwatershed was created using an area-weighted average of NEXRAD P3 precipitation estimates for all HRAP grid cells covering the subwatershed. The SWAT model was calibrated with both NEXRAD P3 data and NCDC precipitation gauge (PG) data from 1 January 2002 to 31 December 2008. The P3-calibrated model was validated using PG data for the same simulation period (2002-2008), and vice versa. The PG-calibrated model yielded slightly higher daily Nash-Sutcliffe efficiency (E(subscript)NS = 0.40) than P3 calibrated model (ENS = 0.35), but the yearly ENS and PBIAS for P3 calibrated model (ENS = 0.80) was much better than PG-calibrated model (ENS = 0.43). The P3-validated model (PG calibration) had yearly ENS = of 0.70, whereas the PGcalibrated model had ENS = 0.43. The daily PBIAS value for P3-calibrated model in 2007 (wet year) was -14.13 and for the P3-calibrated model was -32.83; PG data overestimated the streamflow compared to P3 data in 2007. The P3 data has better agreement with PG data from 2002-2008 period than for 1996-2001 period. The streamflow estimation was better with NEXRAD P3 precipitation data in both calibration and validation runs. Even though the model was calibrated with PG data, the validated model with P3 data has comparatively high ENS. The spatial variation of streamflow response within the watershed was greater compared to the temporal variation in both the calibrated models. The spatial representation of precipitation data by NEXRAD P3 has improved the modeling performance compared to PG data; it is evident that NEXRAD data is an alternative to precipitation gauge measurements.
Keywords: NEXRAD; P3; Precipitation; Spatial Resolution; SWAT; Simulation; Engineering, Environmental (0775)